Experimental Study of Surface Roughness of Triboelectric Nanogenerator - Xu, Ziyue (International Journal of Electric Power and Energy Studies, 2024)
Ecoflex Silicone rubber with various surface roughness was prepared and subjected to TENG testing with ITO coated with copper foil. Dektak XT was used to test thickness Pa and Pq values for different surface roughness levels. The samples are labelled as Sample_REF, Sample_P1200, Sample_P500, and Sample_P320 respectively according to the different sandpapers used. TENG devices were used to obtain four sets of samples corresponding to the voltage and current of the TENGs with an active area of 2.5cm × 2.5cm will be assessed under a fixed working condition. Finally, the electrical properties of each sample were compared to obtain the relationship between surface roughness and output performance.